Human immunodeficiency virus and carotid artery disease - single center experience and literature review - Pereira-Neves,António (2022)
Abstract Introduction: People infected with the human immunodeficiency virus (HIV) - People living with HIV/AIDS (PLWHA) - seem to have an increased risk of incidence and prevalence of cardiovascular diseases, namely stroke of ischemic nature. Additional etiological mechanisms, in addition to aging, appear to lie in chronic virus-mediated inflammation as well as in antiretroviral therapy (ART). The aim of this study was to carry out a retrospective review with descriptive analysis of cases of PLWHA and with a diagnosis of carotid atherosclerotic disease in a tertiary referral center as well as a non-systematic review of the literature. Methods: All patients diagnosed with HIV infection and concomitantly diagnosed with carotid atherosclerotic disease, in a tertiary center, between October 2007 and December 2019, were selected. A descriptive analysis of the sample and additionally a non-systematic review of the literature using the MEDLINE database, were performed. Results: Nine patients who met the inclusion criteria were selected, 7 (78%) being male. The mean age at diagnosis of carotid disease was 59 years. The diagnosis of HIV infection preceded, on average, 12 years before the diagnosis of carotid disease, while the start of ART preceded this diagnosis by about 11 years. The most common cardiovascular risk factors are dyslipidemia (89%), high blood pressure (56%) and smoking (56%). Approximately 33% had peripheral arterial disease and 22% had coronary artery disease. Only two (22%) patients underwent carotid endarterectomy over a median follow-up of 5 years, both for asymptomatic stenosis. Since the diagnosis of carotid disease, there have been no major cardiovascular events (stroke or acute myocardial infarction). During follow-up there were two deaths. Conclusion: PLWHA have a high prevalence of multisite artery disease, manifesting it at a relatively earlier age compared to the general population. These patients benefit from multidisciplinary follow-up for therapeutic optimization in order to obtain better results. However, larger prospective studies are needed to clarify the results in these patients and to improve the therapeutic approach, particularly in those with concomitant carotid disease.